STRATEGI PEMASARAN JASA PENDIDIKAN DI SMA ISLAM PANGLIMA BESAR SOEDIRMAN 1 BEKASI - Muhamad Faisal Ershadwi Satria; Winda Dewi Listyasari; Heldy Ramadhan Putra (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
This research is located in SMA Islam Panglima Besar Soedirman 1 Bekasi. This research aims to perceive and obtain empirical data related to marketing strategy in educational service and market positioning. This research is conducted since March 2017 until July 2017. The approach that used in this research is qualitiatve with descriptive method. Data collection is done through interview, observation, and documentation study. The sources of research data came from key informants namely the headmaster of Islamic Senior High School Panglima Soedirman 1 Bekasi, as well as several supporting informants namely Vice Principal of Student Affairs, Vice Principal of Curriculum and Vice Principal Division of Public Relations and Infrastructure. The results of this study indicate that: (1) market segmentation analysis conducted by SMA Islam Panglima Besar Soedirman 1 Bekasi includes demographic segmentation including segment of education level, economic level, religion and geographical segmentation covering residence segment, (2) SMA Islam Panglima Besar Soedirman 1 Bekasi determines the target market by evaluating the attractive segment, (3) SMA Islam Panglima Besar Soedirman 1 Bekasi determines the market position by showing the superiority and characteristic owned such as school achievement, complete facilities, curriculum with additional religious education Islam, and the quality of schools that have received "A" accreditation and ISO 9001: 2015 certificates, and submitted them to specified target markets. Keywords: Marketing Strategy, Market Segmentation, Targeting, Positioning